Association of clinician diagnostic performance with machine learning-based decision support systems: a systematic review - Vasey, B; Ursprung, S; Beddoe, B; Taylor, EH; Marlow, N; Bilbro, N; Watkinson, P; McCulloch, P (American Medical Association, 2021)
Importance: An increasing number of machine learning (ML)-based clinical decision support systems (CDSSs) are described in the medical literature, but this research focuses almost entirely on comparing CDSS directly with clinicians (human vs computer). Little is known about the outcomes of these systems when used as adjuncts to human decision-making (human vs human with computer).